Biophysical regulations of transpiration and water use strategy in a mature Chinese pine (Pinus tabulaeformis) forest in a semiarid urban environment. Issue 2 (30th January 2022) - Chen, Shengnan; Chen, Zuosinan; Xu, Hang; Kong, Zhe; Xu, Zhibin; Liu, Qingquan; Liu, Pingsheng; Zhang, Zhiqiang
Abstract: Urban trees and forests provide multiple ecosystem services for urban dwellers. However, forest water use for these benefits has become one of the critical concerns in dryland regions where water is limited. Negative forest water use impacts could be reduced by selecting tree species with low rates of transpiration. However, the possible changes of urban tree transpiration and its biophysical controls are still unclear. This study monitored the sap flow of a 58‐year‐old Chinese pine ( Pinus tabulaeformis ) plantation in a semiarid urban environment of northern China. Soil moisture played an important role in stand transpiration ( E c ). E c had a strong positive relationship with vapour pressure deficit ( VPD ) and solar radiation ( R s ) when soil water was sufficient. In addition, the sensitivity of leaf stomata to VPD was not related to leaf and branch water potential. Under soil water stress, E c was significantly reduced by 63.1% ( p  < 0.001) and was weakly related to VPD and R s . Canopy conductance ( g c ) was reduced ( p  < 0.001) by 74.3% due to leaf stomatal closure, and the sensitivity of leaf stomata to VPD was significantly increased ( p  < 0.05) with increasing leaf and branch water potential. Wind speed had no significant effects on E c . P. tabulaeformis tended to be isohydric with a relatively constant midday leaf water potential (i.e. −2.46 to −2.92 MPa) and strong stomatal regulation as a function of soil water stress. However, slopes (0.53–0.56) of the linear relationship between m (d g c /dln VPD ) and reference canopy conductance were significantly lower than the widely recognized 0.6 ( p  < 0.001). Therefore, urban tree transpiration drivers and forest impacts need to be clarified to better understand the proper tradeoff between water consumption and ecological services for urban areas. Abstract : Soil water availability altered forest transpiration response to climatic conditions. Stomatal openness could be inhibited by the decrease of leaf and branch water potential during drought stress. Pinus tabulaeformis tended to an isohydric water use behaviour with the constant leaf water potential and strict stomatal regulation in urban environments.